2020
DOI: 10.1111/caim.12362
|View full text |Cite
|
Sign up to set email alerts
|

From the classical art to the urban art infusion effect: The effect of street art and graffiti on the consumer evaluation of products

Abstract: Combinations of art and products are a classic and current topic. Examples like the collaboration of the Medici with artists in the Renaissance or the logo development of Chupa Chups by Salvador Dali are historical examples. The BMW art cars by Jeff Koons and Cao Fei or the art-based special editions of Louis Vuitton bags are current best practices. All these cases expected a positive impact of art on the product or brand evaluation. This spillover effect was coined "art infusion effect" by Hagtvedt and Patric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Then, they demonstrated that products displayed with art infusion are perceived as more luxurious and purchasable. Baumgarth and Wieker (2020) also confirmed the effects of art infusion using urban art elements on luxury perception and product evaluation.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Then, they demonstrated that products displayed with art infusion are perceived as more luxurious and purchasable. Baumgarth and Wieker (2020) also confirmed the effects of art infusion using urban art elements on luxury perception and product evaluation.…”
Section: Introductionsupporting
confidence: 62%
“…They also found that consumers' desire to signal status and desire for distinction moderates their relationship between art infusion and willingness to buy. In another study, Baumgarth and Wieker (2020) found that urban art elements in product design affect luxury perception. Based on these findings, the following hypothesis is proposed:…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…The art infusion effect (Hagtvedt & Patrick, 2008) is a special kind of spillover effect according to which consumers' associations with (typically classical fine) arts are transferred to a product/brand if the art and the product/brand are jointly communicated. Baumgarth and Bahati Wieker (2020) investigate whether the art infusion effect can be generalized to urban art such as street art and graffiti. Based on a small survey, the authors can confirm such generalization.…”
Section: Eleven Studies Dealing With Intersections Of Marketing and Dmentioning
confidence: 99%
“…The most important megatrends are digitalisation, changing values and new business models, which results in completely new questions and challenges for brand management. 'Hot' topics include the loss of brand control by external stakeholders (keywords: Firestorms in social media, brand hate, brand co-creation; e.g., Dessart et al, 2020;Herhausen et al, 2019;Ind et al, 2017;Ind & Schmidt, 2019;Kristal et al, 2018Kristal et al, , 2020Zarantonello et al, 2016), more complex customer journeys through off-and online brand touchpoints (keywords: ZMOT, customer journey, brand and customer experience; e.g., Lecinski, 2011;Lemon & Verhoef, 2016), new digital brand contact points (keywords: voice assistants and robots; e.g., Kuehnl et al, 2019;McLeay et al, 2020;West et al, 2018), the legitimacy crisis of purely profit-oriented business models and brands (keywords: Fridays for Future, Black Lives Matter, brand purpose, political brands; e.g., Hsu, 2017;Matos et al, 2017), new types of collaboration (keywords: art-brand-collaborations, influencer; e.g., Baumgarth, 2018;Baumgarth & Wieker, 2020;Ki et al, 2020;Michel & Willing, 2020;Nascimento et al, 2020) and building brands for new companies and new business models (keywords: start-up or entrepreneurial branding, vegan and meat alternatives, platform brands, direct-to-consumer brands; e.g., Eggers et al, 2016;Haslehurst et al, 2017;Kühlwein, 2019;Van Loo et al 2020). These and many other new topics lead to new and exciting questions for brand science.…”
Section: Fresh Topicsmentioning
confidence: 99%